Incidence and Risk Factors for the Development of New-Onset Diabetes after Kidney Transplantation - Elamouri, Jamila S. (Journal of Diabetes and Endocrine Practice, 2023)
Objective New-onset diabetes mellitus after transplantation (NODAT), also known as posttransplant diabetes mellitus, is a common complication after kidney transplantation. It is associated with an increased risk of graft failure and death. Therefore, minimizing the risk of NODAT is a priority after kidney transplantation. This study aimed to determine the incidence of NODAT, the risk factors for its development, and the therapeutic drugs used for its management.Patients and Methods This is an observational, retrospective study on kidney recipients who were followed up in our center in 2021. After excluding known diabetic patients, second transplant patients, and those with follow-up periods less than 6 months, 308 recipients were included in the study. Demographic, clinical, and laboratory data were collected from the patient records. The patients were categorized as diabetic or nondiabetic.Results All patients' mean age was 35.9±11.6 years (standard deviation). The male-to-female ratio was 2.13:1. The overall incidence of NODAT was 38.3%. The median time to NODAT diagnosis was 6 months. Patients older than 40 were more likely to develop NODAT (61.1%; p = 0.000). The prevalence of pretransplant body mass index (BMI) more than 25 was significantly higher (67.6%) in diabetic than among nondiabetic patients (p = 0.000). NODAT patients were more likely to have had a rejection episode (65 vs. 35% in nondiabetic patients; p = 0.011). A high trough level of calcineurin inhibitors carried a significant risk of NODAT development. Tacrolimus trough level more than or equal to 10 ng/mL had an odds ratio of 57.9 (95% confidence interval [CI] 7.689–1262.2; p = 0.0007) for the development of NODAT. Likewise, a cyclosporine-A trough level more than or equal to 150 ng/mL had an odds ratio of 100.7 (95% CI: 7.31–4293.5; p = 0.0028).Conclusion NODAT incidence was high in this study. Older age, high BMI, prior rejection episode, steroid dose, and high calcineurin inhibitors trough levels were significant risk factors for developing NODAT.
Keywords: new-onset diabetes after transplantation; tacrolimus; cyclosporine-A; kidney transplant; calcineurin inhibitors